Factors Affecting Ownership of Healthy Latrines in the Semerup Community Health Center, Kerinci Regency - Fajrina Hidayati; Fitria Eka Putri; Hubaybah; Oka Lesmana S; Fiona Syahri Fedhila (PT Inovasi Pratama Internasional, 2022)
One of the sanitation facilities that must be owned by every household is a healthy latrine. The low coverage of latrine ownership causes health problems, one of which is diarrhea. Semurup Health Center is one of the health service facilities in Kerinci Regency. In the working area of ​​the Puskesmas Semerup, the coverage of latrine ownership is 55% and is still relatively low, although triggers are often carried out by health workers from the puskesmas or health department. The purpose of this study was to determine the factors that influence the ownership of latrines in the working area of ​​the Semerup Health Center, Kerinci Regency. This research is a quantitative research with a cross sectional approach. The population in this study is the head of the family in Balaii Village totaling 242 families. The sample in this study was 79 households, and the sampling technique used a simple random sample. The results of this study are that there is a relationship between education (p.value = 0.003), knowledge (p.value = 0.000) and attitudes (p.value = 0.000) with ownership of healthy latrines, and than there is no relationship between the role of health workers (p.value=0.055) and ownership of healthy latrines in the working area of ​​the Semerup Health Center, Kerinci Regency.